BIROKRASI DAN POLITIK DALAM TATA KELOLA PEMERINTAHAN: IMPLEMENTASI SISTEM MERIT PADA KEMENTERIAN HAK ASASI MANUSIA - Kartika, Cindy; Azzahra, Dhara Fatimah; Ferrysca, Najwa Aqilah; Alianinggrum, Nava Nur (FISIP UPNVJ, 2025)
This article explores the relationship between bureaucracy and politics in the context of administrative reform in Indonesia, focusing on the implementation of the merit system at the Ministry of Human Rights (HAM) following its separation from the Ministry of Law and Human Rights in 2024. The merit system is a crucial tool for establishing a professional, neutral, and competency-based bureaucracy. This study employs a qualitative approach using descriptive case studies. Findings reveal that despite initial efforts such as merit-based civil servant recruitment significant challenges remain, including political interference, lack of integrated personnel data, and budget constraints. Policy recommendations include strengthening oversight, digitizing human resource management, and encouraging public participation to ensure accountability. This research highlights the importance of consistent, objective standards in applying the merit system to achieve good governance.